Evaluation of Somatic Cell Count, Leukocytes, and Exfoliative Secretory Cells in CMT-positive Raw Goat Milk (RGM) with Subclinical Mastitis in Mixed-breed Goats - Cha-umphol, Phinidda; Sanglarpcharoenkit, Montri; Pavasutthipaisit, Suvarin; Chawanit, Mongkol (Journal of Mahanakorn Veterinary Medicine, 2023)
The California Mastitis Testing (CMT) is a routine diagnostic tool for mastitis-screening programs to identify subclinical mastitis using raw milk in dairy cows, sheep, and goats. This research aimed to evaluate total somatic cells, leukocytes, and exfoliative secretory cells in raw goat milk (RGM). The milk specimens were collected from 26 mixed-breed goats in Bangkok and Pathumthani provinces. All dairy goats during mid to late lactation were evaluated using CMT scoring system (negative, T = trace, +1 = mild positive CMT reaction, +2 = moderate positive CMT reaction, +3 = strong positive CMT reaction). Only milk specimens with somatic cell count greater than 2X105 cells/ml were determined with CMT scores +1 to +3. Each RGM specimen was tested twice with CMT solution (2:2ml), followed by leukocyte count and exfoliative secretory cell count using hemocytometer. The average of leukocyte count results revealed RGM with +1 CMT score (n=13) consisting of 2.68 ± 1.07 x106 cells/ml, RGM with +2 CMT score (n=6) consisting of 13.65 ± 6.78 x106 cells/ml, and RGM with +3 CMT score (n=7) was 38.63 ± 22.20 x106 cells/ml. Our results of an average exfoliative secretory cell count showed RGM with +1 CMT score was 2.86 ± 1.56 x105 cells/ml, RGM with +2 CMT score was 2.58 ±0.83 x105 cells/ml, and RGM with +3 CMT score was 2.93 ± 1.46 x105 cells/ml. The average total somatic cell count in RGM was revealed including RGM with +1 CMT score had 2.97±1.13 x106 cells/ml, RGM with +2 CMT score had 13.91 ± 6.71 x106 cells/ml, and RGM with +3 CMT score had 38.92 ± 22.24 x106 cells/ml. Our findings indicated that leukocyte count and total somatic cell count were statistically significant differences between RGM with CMT scores (p<0.05), albeit no significant difference in exfoliative secretory cell count between CMT scores was found. This study provides informative data for further determining the CMT scoring system of RGM to detect caprine subclinical mastitis.